The Effect of Doctor-Nurse Communication on Patient Safety Culture: Study in One Private Hospital in Malang - Indra Ningrum Fitria; Elisabeth Fransiska Sibarani (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
The complexity of health services in hospitals is a safety and safety risk in the form of Unexpected Events (KTD) or Nearly Accidental Events (KNC). One of the factors that can prevent KTD and KNC is doctor-nurse communication as the spearhead of health services in hospitals. This study aims to analyze the effect of doctor-nurse communication (openness, accuracy, timeliness, understanding) on ​​patient safety in hospitals. The design of this research is a cross sectional study. Doctor-nurse communication was measured based on nurses' perceptions using a closed questionnaire. Respondents involved 40 nurses. Data were analyzed using multiple linear regression. The results of the analysis show that the doctor-nurse communication variable has an average of 2.92, meaning that it has been running well. Patient safety culture has an average value of 3.07, which means that patient safety is also going well. The results showed that the communication components (openness, accuracy, timeliness, understanding) did not have a significant effect (adjusted R2 = 0.065, p = 0.176) on safety safety culture simultaneously or partially.